LES SERIES DETRITIQUES DU BASSIN DE L'INDUS AU LADAKH: NOUVELLES DONNEES STRATIGRAPHIQUES ET STRUCTURALES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The study of the Indus detritic series in the western part of the Indus basin, between Khalsi and the Zanskar river allows us to distinguish various lithostratigraphic units. New datations have been obtained in several sedimentar y horizons. Marine deposits ceased at the end of early Eocene (Ilerdian —Cuisian) time; detritical series is mainly continental in feature and younger than early Eocene in age. The Indus formations are folded in a large dissymetric north vergent synclinorium of N 120 orientation; numerous folds and reverse faults are observed. The deformation and the epimetamorphism increase southward close to the northward thrusting of the Indus flysch nappes against the Indus detritics. Two main tectonic phases have been observed.
Keywords: Indus basin; detritic formations; Cretaceous—Tertiary; stratigraphy; tectonic; Indus suture; Ladakh; Himalaya.